Design de interação e a amanualidade em Álvaro Vieira Pinto - Gonzatto, Rodrigo Freese (2014)
This dissertation explores the possibility of using the concept of ‘amanialidade’ (handiness) to understand the fundations of Interaction Design. Developed by Álvaro Vieira Pinto, this concept seeks to grasp social and technological transformation from the handling of artifacts. In thes work we present considerations dor fundations in Interaction Design building on the thought of Vieira Pinto, especially from your handinnes concept, whick dels with the relationship between human beings and the objects aroud, available ‘at hand’. Coming from existencial -phenomenogical philosophy, this concept is already discussed in Interaction Design and Human Computer, Interaction, Mainly by the interpretation made by Terry Winograd and Fernando Flores, in which readinees-to-hand (handiness) is used to understand the existencial dimension of action human use of artifacts in everyday life. The conceptualization of handiness by Vieira Pinto allows the understanding of dimensions of the relationship between people and artifacts, considering the active of individuals in technological development and the widespread socio-historical facet of human existence, by the use and production of artfacts from the work with them. With this aim, we corried out a historical review of the concept of handiness and the foundations in Interaction Design, we analyze how the concept is characterized by Vieira Pinto and we propose a counterpoint between their characterization and how it is proposed by Winograd an Flores, an examples in Interaction Design from the handinees by Álvaro Vieira Pinto.